Optimizing the use of intravenous magnesium sulfate for acute asthma treatment in children. Issue 12 (24th May 2016) - Liu, Xiaoxi; Yu, Tian; Rower, Joseph E.; Campbell, Sarah C.; Sherwin, Catherine M.T.; Johnson, Michael D.
Summary: Background: Asthma is the most common pediatric chronic disease and currently affects 7.1 million children in the United States. Many children experience acute asthma exacerbations. Many children also require hospitalization despite treatment in an emergency department with current standard therapy (corticosteroids, albuterol, and ipratropium). These hospitalizations may be avoided if effective adjunctive therapies can be developed to adequately treat severe exacerbations. Methods: Publications were searched in the PubMed database using the following keywords: magnesium AND asthma AND children AND randomized controlled trial. A total of 30 publications were returned. References of relevant articles were also screened. We included publications of controlled randomized trials where intravenous magnesium sulfate was studied in children (age < 18 years) with acute asthma (n = 7). We excluded studies in adults or trials with other formulations of magnesium (e.g., nebulized). Results: Previous studies have demonstrated that intravenous magnesium sulfate (IV MgSO4 ) significantly improves respiratory function and reduces hospitalization rate in children with moderate to severe asthma exacerbations. Current dosing regimens involve a short infusion of 25–75 mg/kg over 20 min (maximum 2–2.5 g/dose), though no studies have directly compared dosages for relative efficacy. Several studies suggest utilizing a peak plasma concentration of magnesium higher than 4 mg/dL as a surrogate of efficacy. This review summarizes the literature regarding the use of IV MgSO4 for the treatment of pediatric acute asthma. Conclusions: We suggest that optimized dosing regimens could be developed using a linked pharmacokinetic–pharmacodynamic modeling and simulation approach. We propose the factors that should be considered in future clinical trial design in order to better understand the use of IV MgSO4 in pediatric acute asthma.Pediatr Pulmonol. 2016;51:1414–1421. © 2016 Wiley Periodicals, Inc.